2007
DOI: 10.1590/s0100-67622007000500020
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplastid pigment contents and chlorophyll a fluorescence in Amazonian tropical three species

Abstract: Plants react to changes in light and hydrological conditions in terms of quantity and composition of chloroplastidic pigments, which affects the photosynthetic properties and consequently the accumulation of plant biomass. Thus, the chloroplastidic pigment concentration and chlorophyll a fluorescence of three Amazonian species (Bertholletia excelsa, Carapa guianensis e Dipteryx odorata) were investigated in sun and shade leaves form the tree crown collected during two distinct periods of precipitation (dry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 20 publications
6
15
0
4
Order By: Relevance
“…The Fv/Fm values are within the range (0.75 to 0.85) suggested by Bolhar-Nordenkampf et al (1989) to be indicative of unstressed plants. In agreement with these data, Morais et al (2007) also suggested that the dry season of the Amazon region is not sufficient to cause negative alterations in the Fv/Fm ratios of the species evaluated, whose values were also close to 0.8. Statistical analysis indicated the Fv/F0 ratio as the more effective in discriminating the efficiency of the photosynthetic apparatus.…”
Section: Discussionsupporting
confidence: 82%
“…The Fv/Fm values are within the range (0.75 to 0.85) suggested by Bolhar-Nordenkampf et al (1989) to be indicative of unstressed plants. In agreement with these data, Morais et al (2007) also suggested that the dry season of the Amazon region is not sufficient to cause negative alterations in the Fv/Fm ratios of the species evaluated, whose values were also close to 0.8. Statistical analysis indicated the Fv/F0 ratio as the more effective in discriminating the efficiency of the photosynthetic apparatus.…”
Section: Discussionsupporting
confidence: 82%
“…The presence of lower levels of chlorophyll a, b, and total chlorophylls in the EXU is corroborated by the findings of Morais et al (2007), who also observed lower levels of these pigments in tropical tree species (Bertholletia excelsa, Carapa guianensis, and Dipteryx odorata) exposed to increased light intensity. Chlorophyll is constantly synthesized and destroyed in the presence of light (photo-oxidation), but under high light intensity there is a higher rate of decomposition, with the established equilibrium occurring at a lower concentration (Kramer and Kozlowski, 1979).…”
Section: Discussionsupporting
confidence: 70%
“…The decrease in the ratios Chl a:b and Chl total :Carot in plants of C.echinata after periods of exposure to direct sunlight (Figure 4) is one of the immediate responses of shade species when exposed to higher irradiance (Demmig-Adams and Adams, 2006;Morais et al, 2007;Magalhães et al, 2009) light-gathering antennas (Kitajima and Hogan, 2003;Laisk et al, 2005;Magalhães et al, 2009). This strategy protects the photosystems from photo-oxidative damage caused by high irradiance (Tan et al, 2000;Marenco et al, 2001;Reyes-Díaz et al, 2009).…”
Section: Discussionmentioning
confidence: 99%